2013
DOI: 10.1038/ismej.2013.174
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and functional properties of uncultivated MCG archaea assessed by metagenome and gene expression analyses

Abstract: The Miscellaneous Crenarchaeota group (MCG) Archaea is one of the predominant archaeal groups in anoxic environments and may have significant roles in the global biogeochemical cycles. However, no isolate of MCG has been cultivated or characterized to date. In this study, we investigated the genetic organization, ecophysiological properties and evolutionary relationships of MCG archaea with other archaeal members using metagenome information and the result of gene expression experiments. A comparison of the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
210
1
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 247 publications
(227 citation statements)
references
References 32 publications
7
210
1
9
Order By: Relevance
“…One explanation for this trend, one of the most robust in macroecology (Gaston et al, 2000), is related with the alternative concept of 'jack-of-all-trades is master of all' (Brown, 1984;Gaston et al, 1997;Verberk et al, 2010), in which cosmopolitan species that can tolerate a large spectrum of environmental conditions and use a broad range of resources become locally dominant. This concept seems to characterize very well members of the MCG lineage both in terms of resources (Biddle et al, 2008;Lloyd et al, 2013;Meng et al, 2014) and distribution. The MCG lineage was one of the most frequent archaeal lineage found in the sediment habitat as it occurs in 68% (141 sites) of the 207 sediments analyzed.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One explanation for this trend, one of the most robust in macroecology (Gaston et al, 2000), is related with the alternative concept of 'jack-of-all-trades is master of all' (Brown, 1984;Gaston et al, 1997;Verberk et al, 2010), in which cosmopolitan species that can tolerate a large spectrum of environmental conditions and use a broad range of resources become locally dominant. This concept seems to characterize very well members of the MCG lineage both in terms of resources (Biddle et al, 2008;Lloyd et al, 2013;Meng et al, 2014) and distribution. The MCG lineage was one of the most frequent archaeal lineage found in the sediment habitat as it occurs in 68% (141 sites) of the 207 sediments analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…The latter archaeal group, the seventh order of methanogens, are methylotrophic methanogens obtaining energy and carbon from methanol and methylated amines (Paul et al, 2012;Dridi et al, 2012;Iino et al, 2013;Borrel et al, 2014). Although no information on the potential metabolism of the Terrestrial Miscellaneous Euryarchaeotal Group group is available, recent findings from metagenomic data (Meng et al, 2014;Castelle et al, 2015) and single-cell genomics (Lloyd et al, 2013) suggested that members of the MCG and Marine Benthic Group D lineages may be involved in the degradation of detrital proteins both in marine and continental sediments. The high PD of the MCG lineage invalidates any general assumption of potential metabolisms shared between all MCG subgroups (the specialization of certain subgroups towards freshwater and marine habitats is a good example of this).…”
Section: Evolutionary Relationships Between Freshwater and Marine Mcgmentioning
confidence: 99%
See 3 more Smart Citations